Effect of Icariside II and Metformin on Penile Erectile Function, Histological Structure, Mitochondrial Autophagy, Glucose-Lipid Metabolism, Angiotensin II and Sex Hormone in Type 2 Diabetic Rats With Erectile Dysfunction - Jian Zhang, MD; Shuang Li, BS; Shiqing Zhang, MS; Yonghui Wang, BS; Shipeng Jin, BS; Chunli Zhao, MS; Wenzeng Yang, MD; Yuexin Liu, MS; Guangqi Kong, MS (Sexual Medicine, 2020)
Introduction: Type 2 diabetes mellitus erectile dysfunction (T2DMED) is one of the common complications of type 2 diabetes mellitus (T2DM). Icariside II (ICA II), a flavonoid derived from Epimedium, has been shown to improve erectile function in T2DMED rats. Aim: To investigate the effect of ICA II and metformin (MET) on penile erectile function, mitochondrial autophagy, glucose-lipid metabolism in rats with T2DMED. Methods: In the control and T2DMED groups, rats were administered normal saline. In the MET group, rats were administered MET for 0.2 g/kg/day. In the ICA II+MET group, rats were administered ICA II for 10 mg/kg/day and MET for 0.2 g/kg/day. Results: The number of mating rats, number of erectile rats, erection rate, erection frequency, intracorneal pressure, and intracorneal pressure/mean arterial pressure in the ICA II+MET group and control group were significantly higher than corresponding values in than T2DMED group. The absolute values of fasting plasma glucose, glycated haemoglobin in the ICA II+MET group, MET group, and control group were significantly lower than in the T2DMED group. The advanced glycation end product (AGE) values in the ICA II+MET group and the MET group were lower than in the T2DMED group. The receptors for the AGE values and angiotensin II values in the ICA II+MET group were lower than in the T2DMED and MET groups. The high-density lipoprotein values, testosterone values, nitric oxide synthase activity, and cyclic guanosine monophosphate content in the ICA II+MET and control groups were higher than in the T2DMED group. The low-density lipoprotein values, triglyceride values, estradiol values, and total cholesterol values in the ICA II+MET and control groups were lower than in the T2DMED group. Conclusion: ICA II could increase erectile function and smooth muscle cell/collagen fibril proportions, decreased mitochondrial autophagy, and AGE concentrations and improve lipid metabolism, nitric oxide synthase activity, cyclic guanosine monophosphate content, testosterone, estradiol, and Ang II in rat with T2DMED.Zhang J, Li S, Zhang S, et al. Effect of Icariside II and Metformin on Penile Erectile Function, Histological Structure, Mitochondrial Autophagy, Glucose-Lipid Metabolism, Angiotensin II and Sex Hormone in Type 2 Diabetic Rats With Erectile Dysfunction. J Sex Med 2020;8:168–177.